Gene Expression-Based Identification of Antigen-Responsive CD8+ T Cells on a Single-Cell Level - Fuchs, Yannick F.; Sharma, Virag; Eugster, Anne; Kraus, Gloria; Morgenstern, Robert; Dahl, Andreas; Reinhardt, Susanne; Petzold, Andreas; Lindner, Annett; Löbel, Doreen; Bonifacio, Ezio (Frontiers in Immunology, 2019)
CD8+ T cells are important effectors of adaptive immunity against pathogens, tumors and self antigens. Here, we asked how human cognate antigen-responsive CD8+ T cells and their receptors could be identified in unselected single-cell gene expression data. Single-cell RNA sequencing and qPCR of dye-labelled antigen-specific cells identified large gene sets that were congruently up- or downregulated in virus-responsive CD8+ T cells under different antigen presentation conditions. Combined expression of TNFRSF9, XCL1, XCL2, and CRTAM was the most distinct marker of virus-responsive cells on a single-cell level. Using transcriptomic data, we developed a machine learning-based classifier that provides sensitive and specific detection of virus-responsive CD8+ T cells from unselected populations. Gene response profiles of CD8+ T cells specific for the autoantigen islet-specific glucose-6-phosphatase catalytic subunit-related protein differed markedly from virus-specific cells. These findings provide single-cell gene expression parameters for comprehensive identification of rare antigen-responsive cells and T cell receptors.